The media victimisation of the defendant through the violation of the presumption of innocence - Đoković Lazar (Temida)
The paper analyses the theoretical concept and legal framework of the presumption of innocence and the significance of the consequences of its violation by the media in Serbia, which leads to the victimization of the accused. An analysis of examples of reporting of selected electronic media is presented, in which the way the media violates the presumption of innocence is indicated. In order to draw the attention of the professional and general public to the consequences of unethical media reporting on crime, it is pointed out that they are reflected in the impossibility of proper development of the defendant’s personality, stigmatization as a direct consequence of media treatment to which he was exposed, and degradation of the right to privacy. The author concludes that it is necessary to work on raising public awareness of the unforeseeable harmful consequences for the personality of all those who are associated with a criminal event in the media and to more legally regulate the ban on violating the presumption of innocence by the media, and achieve a balance between the presumption of innocence, as a part of the corpus of the defendant’s rights, and the right of the public to be informed on time of the state of crime.